Karakterisasi Biochar dari Ampas Tebu dan Kemampuan Penyerapan Nitrogen Sebagai Amelioran Pada Tanah Gambut Secara In Vitro - Warsidah, Warsidah; Suparnawati, Suparnawati; Aritonang, Anthoni Batahan; Ardiningsih, Puji; Ashari, Asri Mulya; Sofiana, Mega Sari Juane (Innofarm:Jurnal Inovasi Pertanian, 2021)
Research has been carried out on the characterization of biochar pores produced from bagasse through a pyrolysis process at a temperature of 110oC for 4 hours, using the Scaning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX) method. The biochar of sugarcane pulp produced is then tested for its ability to absorb nitrogen content (% N-total), with the source of N is urea fertilizer through the Kjedhal method based on SNI (2801: 2010), and the source of nitrogen from a solution of ammonium sulfate (NH4)2SO4 by the titrimetric method. The SEM measurement results showed that the biochar pores were uniform and micro-sized, while the peat pores were macro in size and irregular. EDX results show that biochar is composed of 100% carbon, while peat soil consists of carbon compounds (C), Oxygen (O) Silica (Si) and Aluminum (Al). Both of biochar and peat have moisture content of 0.38% and 11.79%, ash content of 2.42% AND 24.44%, volatile content of 0.53% and 5.23% of bound or fixed carbon (cf) of 97.02% and 58.53%. The results of the biochar capacity test applied to peat soils can increase the pH of the peat from 5 to 6.5 with the ability to absorb N-total from urea (NH2)2CO and N-total fertilizer sources from ammonium sulfate (NH4)2SO4 solution of 38% - 66%, and 56.5% -84.5%.